Xây dựng mô hình phổ biến, giáo dục pháp luật trong Trường Cao đẳng Sư phạm - Đặng, Cao Sơn; Đặng, Thị Thanh Mai; Trần, Hùng Viện (Tạp chí Giáo dục, 2024)
For vocational education institutions in general and pedagogical colleges in particular, the work of disseminating and educating the law is an important political task of the school, one of the contents of profession education, contributing to creating strong changes in awareness, raising awareness of compliance and strict observance of the law; form the habit of self-discipline in studying and learning about the law; build a lifestyle, study and work according to the law for students, lecturers, educational managers and workers. The article outlines some features of the current situation of legal dissemination and education in pedagogical colleges, thereby showing the need to build and replicate models; at the same time, it proposes steps to build a model, suggest some suitable models for popularizing legal education in pedagogical colleges and illustrate a model that has been effectively implemented in popularizing legal education at Bac Ninh Pedagogical College. Law dissemination and education models are built scientifically and in accordance with training practices, helping the work of law dissemination and education in pedagogical colleges become more substantive and effective.